Pembrolizumab in FIGO IVB Verrucous Carcinoma of the Vulva: A Case Report - Wang, Yuhan; Lin, Rongchun; Zhang, Bingzhong; Zhou, Hui; Lin, Zhongqiu; Yao, Tingting (Frontiers in Oncology, 2021)
Background: Vulvar cancer is the fourth most common gynecologic cancer, and prognosis is poor in advanced vulvar cancer patients. Treatment for advanced vulvar cancer has not been satisfactory. In this report, we firstly report a FIGO ⅣB vulva verrucous carcinoma patient who obtained good prognosis after systemic treatment. Case presentation: A patient was admitted to hospital due to her vulvar lesion persistent for past fourteen years. The vulvar mass has widely invaded urethra, part of anus, the lower third of the vagina, bilateral superior and inferior branches of pubis, and bilateral internal and external muscles of obturator. Multiple metastatic lymph nodes were also found in the pelvic cavity. The histopathological studies confirmed vulvar verrucous carcinoma with a PD-L1 overexpression. After 6 courses of neoadjuvant chemotherapy and pembrolizumab, the patient underwent radical vulvectomy and achieved optimal cytoreduction. Postoperative pathology found no residual tumor. The patient then received one course of postoperative chemotherapy and pembrolizumab, underwent radiation therapy, and was disease free after 6 months follow-up. Conclusion: Our individualized treatment strategy is successful. Pembrolizumab is safe and effective in the treatment of advanced vulvar verrucous carcinoma.